Comparative studies of technological practices between coastal and mediterranean patagonian hunter-gatherer groups - Cueto, Manuel (2015)
Fil: Cueto, Manuel. División Arqueología. Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata; Argentina